2021
DOI: 10.1111/ejn.15496
|View full text |Cite
|
Sign up to set email alerts
|

Human wildtype tau expression in cholinergic pedunculopontine tegmental neurons is sufficient to produce PSP‐like behavioural deficits and neuropathology

Abstract: Progressive Supranuclear Palsy (PSP) is the most common atypical parkinsonism and exhibits hallmark symptomology including motor function impairment and dysexecutive dementia. In contrast to Parkinson's disease, the underlying pathology displays aggregation of the protein tau, which is also seen in disorders such as Alzheimer's disease. Currently, there are no pharmacological treatments for PSP, and drug discovery efforts are hindered by the lack of an animal model specific to PSP. Based on previous results an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…With regard to the function of the PPTg in muscle tone, electrical stimulation of the PPTg could suppress the muscle tone, while the destruction of PPTg released musculature from inhibition and induced abnormal flexion of the spine and limbs in rats ( 17 , 20 , 39 ). In terms of the specific neural population of the PPTg, hindlimb clasping was observed in 100% of rats that underwent viral deposition of tau in cholinergic neurons in the bilateral PPTg ( 40 ). In addition, recent optogenetic studies found that different types of neurons in the PPTg had varied effects on muscle tone, with glutamatergic neurons in the PPTg preferably activated flexor muscles and cholinergic neurons activated extensor muscles ( 8 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the function of the PPTg in muscle tone, electrical stimulation of the PPTg could suppress the muscle tone, while the destruction of PPTg released musculature from inhibition and induced abnormal flexion of the spine and limbs in rats ( 17 , 20 , 39 ). In terms of the specific neural population of the PPTg, hindlimb clasping was observed in 100% of rats that underwent viral deposition of tau in cholinergic neurons in the bilateral PPTg ( 40 ). In addition, recent optogenetic studies found that different types of neurons in the PPTg had varied effects on muscle tone, with glutamatergic neurons in the PPTg preferably activated flexor muscles and cholinergic neurons activated extensor muscles ( 8 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the relatively short duration, dystonia-like behaviors could only be explained by the functional changes of the PPTg-related motor regions. Although persisted hindlimb clasping was found in a rat that underwent bilateral tau expression in cholinergic neurons of the PPTg for 20 weeks ( 40 ), studies with a longer PPTg lesion duration should be conducted for the exploration of the dystonia-like behaviors and its underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, although mice express only 4R tau isomers, rats, like humans, express all six tau isoforms 27 . A recently developed rat model expressing human tau 28 or ideally nonhuman primates may increase success in translation to clinical trials.…”
Section: Definition Of 4r Tauopathies Targetsmentioning
confidence: 99%
“…Additionally, the rigidity of the tail and proximal part of the limb contralateral to the lesioned side also appeared along with the back curvature ( 12 ). Moreover, when wild-type human tau was specifically expressed in the cholinergic neurons of the PPN, rats showed dystonia-like behavior of the hindlimb (hindlimb retracted toward body, crossing, and immobility) while suspended ( 38 ).…”
Section: Preclinical Findings Of the Involvement Of The Ppn In Dystoniamentioning
confidence: 99%